A hidden pygmy devil from the Philippines: Arulenus miae sp. nov.—a new species serendipitously discovered in an amateur Facebook post (Tetrigidae: Discotettiginae) - Skejo, Josip; Caballero, Joy Honezza S. (Zootaxa, 2016)
Arulenus miae Skejo & Caballero sp. nov. is described from Buknidon and Davao, Mindanao, the Philippines. The species was serendipitously found in an amateur photo posted in Orthoptera Facebook group by Leif Gabrielsen. Holotype and paratype are deposited in Nederlands Centrum voor Biodiversiteit in Leiden, the Netherlands. Detailed comparison with Arulenus validispinus Stål, 1877 is given. A new diagnosis of the genus and A. validispinus is given. The paper is part of the revision of the subfamily Discotettiginae. This study provides a good example of how social networks can be used as a modern tool of discovering biodiversity if the regulations of the International Code of the Zoological Nomenclature are followed. A brief insight into habitat and ecology of this rainforest and mountainous species is presented.